Final answer:
To solve the system of equations y=-2x+2, y=7x+11 by substitution, substitute the value of y from the first equation into the second equation. The solution is x=-1 and y=4.
Step-by-step explanation:
To solve the system of equations y = -2x + 2 and y = 7x + 11 by substitution, we will substitute the value of y from the first equation into the second equation.
Substitute -2x + 2 for y in the second equation:
7x + 11 = -2x + 2
Combine like terms:
9x = -9
Divide both sides by 9:
x = -1
Substitute x = -1 back into the first equation to find y:
y = -2(-1) + 2
y = 4
The solution to the system of equations is x = -1 and y = 4.